Data retrieval from archival renal biopsies using nonlinear microscopy. - Lucas C Cahill; Tadayuki Yoshitake; Milan Rosen; Timothy D Weber; James G Fujimoto; Seymour Rosen (PLoS ONE)
Thorough examination of renal biopsies may improve understanding of renal disease. Imaging of renal biopsies with fluorescence nonlinear microscopy (NLM) and optical clearing enables three-dimensional (3D) visualization of pathology without microtome sectioning. Archival renal paraffin blocks from 12 patients were deparaffinized and stained with Hoechst and Eosin for fluorescent nuclear and cytoplasmic/stromal contrast, then optically cleared using benzyl alcohol benzyl benzoate (BABB). NLM images of entire biopsy fragments (thickness range 88-660 μm) were acquired using NLM with fluorescent signals mapped to an H&E color scale. Cysts, glomeruli, exudative lesions, and Kimmelstiel-Wilson nodules were segmented in 3D and their volumes, diameters, and percent composition could be obtained. The glomerular count on 3D NLM volumes was high indicating that archival blocks could be a vast tissue resource to enable larger-scale retrospective studies. Rapid optical clearing and NLM imaging enables more thorough biopsy examination and is a promising technique for analysis of archival paraffin blocks.